2019
DOI: 10.1021/acsami.9b03385
|View full text |Cite
|
Sign up to set email alerts
|

Surfaces that Adhesively Discriminate Breast Epithelial Cell Lines and Lymphocytes in Buffer and Human Breast Milk

Abstract: We report new surface coatings that adhesively distinguish three breast epithelial cell lines (MCF-10A, MCF-7, TMX2–28) when cell suspensions in buffer or breast milk are flowed over the coatings. We also report selective capture of epithelial cells and rejection of Jurkat lymphocytes, with average selectivities exceeding 60 and captured cell purities of often exceeding 99+ %. The surfaces achieve the dual goals of selective cell capture and resistance to fouling by proteins and other components of breast milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…A 100 ppm solution of poly- l -lysine hydrobromide (PLL, from Sigma-Aldrich, 15 000–30 000 g/mol nominal molecular weight) was flowed through the chamber at a wall shear rate of 5 s –1 for 10 min, more than sufficient to saturate the surface, and then flowing buffer was returned to the chamber. We previously demonstrated that this procedure produces an adsorbed layer of PLL of about 0.4 mg/m 2 , which is flat (within a few nanometers of the surface), and is not removed, in the time frame of a few hours, upon exposure to a buffer of a variety of ionic strengths; , flowing micro- or nanoparticles; and a variety of negatively charged proteins, mammalian cells, or bacteria such as Staphylococcus aureus …”
Section: Methodsmentioning
confidence: 99%
“…A 100 ppm solution of poly- l -lysine hydrobromide (PLL, from Sigma-Aldrich, 15 000–30 000 g/mol nominal molecular weight) was flowed through the chamber at a wall shear rate of 5 s –1 for 10 min, more than sufficient to saturate the surface, and then flowing buffer was returned to the chamber. We previously demonstrated that this procedure produces an adsorbed layer of PLL of about 0.4 mg/m 2 , which is flat (within a few nanometers of the surface), and is not removed, in the time frame of a few hours, upon exposure to a buffer of a variety of ionic strengths; , flowing micro- or nanoparticles; and a variety of negatively charged proteins, mammalian cells, or bacteria such as Staphylococcus aureus …”
Section: Methodsmentioning
confidence: 99%
“…CO is one of the most common toxic gases and harmful to environment and human health. The elimination of CO and especially the oxidation of CO, a simple and typical reaction in heterogeneous catalysis, has attracted wide attention in recent years due to its academic value and possible applications [9][10][11][12][13]. Progress in nanotechnology provides a precious tool for the study of CO oxidation at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…The cationic PLL backbones adsorb to the negatively charged silica, effectively tethering the PEG side chains. The resulting end-tethered layers of PEG chains have been proven, in many previous studies in our lab ,,, and the laboratories of others, ,, to be exceptionally stable over the conditions and time scales of the experiments, including exposure to varied ionic strengths, pH values, polymer solutions, particles, bacteria, and mammalian cells. In the current studies, no bacterial cells adhered to the coatings, an indication of both the robustness and stability of the PEG layers.…”
Section: Methodsmentioning
confidence: 79%